2009
DOI: 10.1007/s11771-009-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis and structural characterization of urea-isobutyraldehyde-formaldehyde resin

Abstract: Urea-isobutyraldehyde-formaldehyde (UIF) resin was synthesized from urea, isobutyraldehyde, and formaldehyde using sulfuric acid as a catalyst by one pot method. The effects of molar ratios of isobutyraldehyde to formaldehyde (n(I)/n(F)) and aldehyde to urea (n(A)/n(U)) on the yield, hydroxyl value (vs KOH) and softening point of the resin were investigated. The structure of the resin was characterized by FT-IR, 1 H-NMR and 13 C-NMR. The results show that when the molar ratio of urea to isobutyraldehyde to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The reactive aliphatic hydroxyl, phenolic hydroxyl and carbonyl groups in alkali lignin make it possible to participate in the reaction of urea-formaldehyde resin synthesis. Yanfang Zhang et al [5] modified the synthesis of urea-formaldehyde by adding lignosulfonate, and results showed that the adhesive had the highest tensile strength of 8.67MPa when the amount of lignin was 30%, and the free formaldehyde content was 0.18%, which was the minimum value when 40% of sulfonated lignin was added. Gramineae alkali lignin was also used to modify urea-formaldehyde adhesive by Jianzhang Li [6], and the modified adhesive had good properties and was suitable for plywood production, dry and wet binding strength were rather high when lignin amount was 30%.…”
Section: Introductionmentioning
confidence: 99%
“…The reactive aliphatic hydroxyl, phenolic hydroxyl and carbonyl groups in alkali lignin make it possible to participate in the reaction of urea-formaldehyde resin synthesis. Yanfang Zhang et al [5] modified the synthesis of urea-formaldehyde by adding lignosulfonate, and results showed that the adhesive had the highest tensile strength of 8.67MPa when the amount of lignin was 30%, and the free formaldehyde content was 0.18%, which was the minimum value when 40% of sulfonated lignin was added. Gramineae alkali lignin was also used to modify urea-formaldehyde adhesive by Jianzhang Li [6], and the modified adhesive had good properties and was suitable for plywood production, dry and wet binding strength were rather high when lignin amount was 30%.…”
Section: Introductionmentioning
confidence: 99%